Bioactive hydrolysates from chlorella vulgaris: optimal process and bioactive properties - Cunha, Sara A. (2022)
Microalgae have been described as a source of bioactive compounds, such as peptides. Microalgae are easy to produce, making them a sustainable resource for extracting active ingredients for industrial applications. Several microalgae species have interesting protein content, such as Chlorella vulgaris with around 52.2% of protein, making it promising for peptide hydrolysate production. Therefore, this work focused on the production of water-soluble hydrolysates rich in proteins/peptides from the microalgae C. vulgaris and studied bioactive properties. For that, a design of experiments (DOE) was performed to establish the optimal conditions to produce hydrolysates with higher levels of protein, as well as antioxidant and antihypertensive properties. Four experimental factors were considered (cellulase percentage, protease percentage, hydrolysis temperature, and hydrolysis duration) for three responses (protein content, antioxidant activity, and antihypertensive activity). The optimal conditions determined by the DOE allowed producing a scaled-up hydrolysate with 45% protein, with antioxidant activity, measured by oxygen radical absorbance capacity assay, of 1035 µmol TE/g protein, IC50 for angiotensin-converting enzyme inhibition activity of 286 µg protein/mL, and α-glucosidase inhibition of 31% (30 mg hydrolysate/mL). The obtained hydrolysates can be used as functional ingredients for food and nutraceuticals due to their antioxidant, antihypertensive, and antidiabetic potential. Moreover, the antioxidant potential of the extracts may be relevant for the cosmetic industry, especially in antiaging formulations.